Baroreflex sensitivity is associated with post-stroke infections: an open, prospective study - Sykora, Marek; Siarnik, Pavel; Szabo, Jozef; Turcani, Peter; Krebs, Stefan; Lang, Wilfried; Jakubicek, Stanislava; Czosnyka, Marek; Smielewski, Peter (Journal of the neurological sciences, 2019)
Background and purpose - Autonomic nervous system (ANS) seems to play an important role in the post-stroke immunosuppression syndrome with increased susceptibility to infections. The aim of this study was to investigate if ANS activity measured at admission is associated with post-stroke infections. - Methods - We prospectively analyzed patients with acute ischemic stroke. ANS was measured using the cross-correlational baroreflex sensitivity (BRS) at admission. The occurrence and cause of in-hospital infections was assessed based on the clinical and laboratory examination. Demographic and clinical variables including initial stroke severity, dysphagia, procedures as nasogastric tubes, central venous and urinary catheters and mechanical ventilation were included in the analysis. - Results - We included 161 patients with ischemic stroke, of those 49 (30.4%) developed a nosocomial infection during the first 7days of hospital stay. Patients with infections had significantly lower BRS (median 3 vs 5ms/mmHg, p<.001) higher initial NIHSS (median 15 vs 5, p<.001), had more often non-lacunar etiology and underwent more invasive procedures. In the multivariable regression model decreased BRS (adjusted OR 1.21, 95% CI 1.03-1.41, p=.02), admission NIHSS (adjusted OR 1.10, 95% CI 1.02-1.19, p=.02) and invasive procedures (adjusted OR 1.46, 95% CI 1.03-2.06, p=.03) were independently associated with infection after ischemic stroke. - Conclusions - Decreased BRS was independently associated with infections after ischemic stroke. Autonomic shift may play an important role in increased susceptibility to infections after stroke. The possible diagnostic and therapeutic relevance of this finding deserves further research.
Gesehen am 21.01.2020